HOMOMORFISMA DAN ANTI-HOMOMORFISMA DARI LEVEL SUBGRUP DALAM SUBGRUP FUZZY - Achmad Riduansyah; Na'imah Hijriati; Saman Abdurrahman (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2015)
One development of algebra is to combine the concept of algebra with the concept of fuzzy set. Some researchers have also found the development of the fuzzy set in algebraic fields, including fuzzy subgroups. Furthermore, in the subgroup fuzzy known subgroup level is a subgroup of the group. This study proves the image and pre-image homomorphism and anti homomorphism of the subgroup level in fuzzy subgroups. The study was conducted by studying literature from various sources, both books and journals that support and relevant to the review conducted. Based on the research conducted by some properties of image and pre-image homomorphism in the fuzzy subgroup is a fuzzy subgroup, a fuzzy subset of ββ is a fuzzy subgroup of ???????? if and only if the fuzzy subset level of bβ (ββ????????) is a subgroup of ????????, if ???????? group and subgrup from ???????? then there is a fuzzy βgubsubsup of so such that ββ???????? = ???????? for every ????????∈ [0,1] and the image and pre-image homomorphism and anti-homomorphism of the subgroup level are subgroup level.